Understanding valvular heart disease in the dental setting. (5th February 2021) - Truong, T; Koh, Y; Yosufi, R; Marangou, J; Slack‐Smith, L; Katzenellenbogen, JM
Abstract: Background: Limited evidence is available regarding dentists' knowledge and interpretation of infective endocarditis (IE) prophylaxis guidelines. The aim of this study was to determine understanding and management of rheumatic and non‐rheumatic valvular heart disease (VHD) in the dental setting in Western Australia (WA). Methods: A cross‐sectional survey of dentists within Perth utilized an online Qualtrics questionnaire developed after consultation with stakeholders. A sampling frame was compiled from the Australian Health Practitioner Regulation Agency with contact details obtained from the White Pages (online), using five quintiles of Socio‐Economic Indexes for Areas according to dentist's place of practice. Results: Of 41 (13.7% of 300 approached) dentists completing the survey (95.1% general dentists, mean years of practice = 15.6), 90.2% reported following the Australian Therapeutic Guidelines (ATG) regarding IE antibiotic prophylaxis in VHD. Most (92.7%) were unaware of the rheumatic heart disease (RHD) control program. Nearly all participants indicated prophylaxis for clearly invasive procedures such as tooth extraction (100.0%) and periodontal surgery (95.1%). Many dentists made the decision to prescribe antibiotics themselves (36.6%). Conclusions: The majority of dentists followed the ATG's IE prophylaxis recommendations for cardiac lesions and dental procedures. There was limited knowledge of the national RHD guidelines and the WA RHD control program.